The effect of the coupling scheme on coupling efficiency and tolerant misalignment of semiconductor optical amplifiers module - Zainal, Jasman; Fadhali, Mohamed M.; Ali, Jalil; Abd. Rahman, Rosly (Faculty of Science, 2008)

(untitled)
Analysis on three different coupling systems, i.e., butt, single ball lens, and two ball lenses was carried out to study their effect in pigtailing a semiconductor optical amplifier (SOA) module. By placing the coupling system between the tips of two coupled single mode fiber parameters such as coupling efficiency and longitudinal tolerant with variation of working distance can be investigated. Result of the three schemes studied showed that two ball lenses is the most efficient for this application even with the assumption of an elliptical beam profile for the source fiber. We also observed an optimum range for the separation between the two lenses at which the coupling efficiency is maximal.